Track-etched membrane-based dual-electrode coulometric detector for microbore/capillary high-performance liquid chromatography - Mizuguchi, Hitoshi; Nishimori, Daichi; Kuwabara, Tomohiko; Takeuchi, Masaki; Iiyama, Masamitsu; Takayanagi, Toshio (Analytica chimica acta, 2020)
The electrochemical flow cell containing track-etched microporous membrane electrodes was applied to a dual-electrode coulometric detector for microbore/capillary HPLC with a small injection volume and low eluent flow rate. The proposed flow cell with a 0.1-mm diameter inlet channel gave a detection volume of 0.08 nL per electrode, which was determined by the eluent flow through the electrode. For the dual-electrode detector, the calculated volume was 0.24 nL. The efficiency of electrooxidation of l-ascorbic acid increased as the flow rate decreased and was close to 100% when the flow rate was below 50 μL min−1, which is a common flow rate in microbore or capillary liquid chromatography. Catecholamines, such as noradrenaline, adrenaline, and dopamine, were detected by total conversion with two-electron oxidation in the potential range from 0.8 to 1.0 V vs. Ag/AgCl after separation with a microbore column. These peaks were accompanied by corresponding cathodic peaks derived from quasi-stable electrooxidation products of the catecholamines. The detection limits of noradrenaline, adrenaline, and dopamine were 0.1, 0.1, and 0.2 μM, respectively. The RSD values for five replicate measurements of 5.0 μM of these compounds were 0.9%, 0.7%, and 1.5%, respectively. Coulometric detection was also demonstrated by determination of catecholamines in pharmaceuticals. [Display omitted] •Construction of a dual-electrode coulometric detector for microbore/capillary HPLC.•The estimated detection volumes were 0.08 nL per electrode and 0.24 nL for the dual-electrode detector.•The efficiency of electrooxidation of l-ascorbic acid was close to 100% at flow rates lower than 0.05 mL min−1.•Observation of chromatograms based on total electrooxidation and corresponding cathodic responses in microbore HPLC.•Demonstration of the calibration-free determination of catecholamines by microbore HPLC-coulometric detection.